STRENGTHENING YOUTH EMPOWERMENT THROUGH OPTIMIZATION OF THE ROLE OF SPORTS EDUCATION IN THE AGE OF COMMUNITY 5.0: MEMPERKUAT PEMBERDAYAAN GENERASI MUDA MELALUI OPTIMISASI PERAN PENDIDIKAN OLAHRAGA DALAM ERA MASYARAKAT 5.0 - Aliriad, Hilmy (UPMI Proceeding Series, 2023)
Sports education has an important role in strengthening the empowerment of the younger generation, especially in the context of the 5.0 Society era. The Era of Society 5.0 refers to the fusion of the physical world and the digital world, where information and communication technologies are rapidly developing and shaping the interaction between people and technology. The purpose of this study is to provide a deep understanding of the importance of sports education in strengthening the empowerment of the younger generation in the era of Society 5.0. Provide insight into the use of information and communication technology as well as innovative approaches in sports education that can increase its effectiveness in achieving the goal of empowering the younger generation. This study uses qualitative research methods that involve the following steps: literature review, research design, data collection, data analysis, and interpretation and discussion of research results. The sample in this study was second semester students, amounting to 50 students of the 2022 batch of the Physical Education and Recreation Study Program at Nahdlatul Ulama Sunan Giri University, Bojonegoro. The results showed that sports education has a positive impact on the physical and mental health of the younger generation. As many as 80% of respondents revealed that sports education has a positive effect on their physical and mental health. 70% also consider sports education to be an important contribution to their social and emotional development. A total of 65% of respondents believe that sports education can prepare them for the challenges at hand. Summary Sports Education has an important role in facilitating the learning and empowerment of young people. Active interaction between sports educators and the younger generation, diverse teaching approaches, as well as positive group dynamics are important factors in creating an effective sports education environment. sports education is an important element in preparing young people to face changes in the era of modern society.